2009
DOI: 10.1103/physrevb.80.064419
|View full text |Cite
|
Sign up to set email alerts
|

Spin-liquid and magnetic phases in the anisotropic triangular lattice: The case ofκ(ET)2X

Abstract: The two-dimensional Hubbard model on the anisotropic triangular lattice, with two different hopping amplitudes t and t ′ , is relevant to describe the low-energy physics of κ-(ET)2X, a family of organic salts. The ground-state properties of this model are studied by using Monte Carlo techniques, on the basis of a recent definition of backflow correlations for strongly-correlated lattice systems. The results show that there is no magnetic order for reasonably large values of the electron-electron interaction U … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(93 citation statements)
references
References 45 publications
4
88
1
Order By: Relevance
“…As mentioned above, previous works have shown (i) suppression of pair-pair correlations within the effective ρ = 1 model [17][18][19][20] , and (ii) the possibility of a fluctuating CO within models focusing on the monomer molecules 33,34,[36][37][38] . We therefore construct pair creation operators that allow unequal charge densities on the monomer molecules that constitute a dimer in Fig.…”
Section: B Pair-pair Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, previous works have shown (i) suppression of pair-pair correlations within the effective ρ = 1 model [17][18][19][20] , and (ii) the possibility of a fluctuating CO within models focusing on the monomer molecules 33,34,[36][37][38] . We therefore construct pair creation operators that allow unequal charge densities on the monomer molecules that constitute a dimer in Fig.…”
Section: B Pair-pair Correlationsmentioning
confidence: 99%
“…A necessary condition for SC within any interacting electrons model however is that interactions must enhance superconducting pair-pair correlations relative to the noninteracting model. Precise numerical calculations within the 1 2 -filled band Hubbard model on triangular lattices have shown that pair-pair correlations decrease with Hubbard U for all anisotropy [17][18][19][20] , thus indicating the need for going beyond the effective 1/2-filled band model in our search for the the mechanism of SC in κ-(ET) 2 X.…”
Section: Introductionmentioning
confidence: 99%
“…Recall that within existing mean field theories the AFM-to-SC transition is driven by spin fluctuations [13][14][15][16][17][18][19][20][21][22][23] , while the CO-to-SC transition is driven by charge fluctuations 65 . Even if we ignore that recent precise numerical calculations [25][26][27] have demonstrated the absence of SC within the proposed spin-fluctuation models in this context (thereby raising doubts also about mean-field theory of charge-fluctuation mediated superconductivity), different mechanisms of SC for structurally related materials with identical or nearidentical molecular components appear to be unrealistic. Within our proposed scenario, the charge-ordered or VBS systems that exhibit SC are PECs in the semiconducting state, while the AFM systems under pressure transform to PECs first and then to SC (although due to actual crystal structures the "width" of the PEC region could be narrow to vanishing within the latter).…”
Section: Consequence Of Stronger Frustration-paired Electron Liquid Amentioning
confidence: 99%
“…It has been claimed that this transition explains the SC in the CTS [13][14][15][16][17][18][19][20][21][22][23][24] . Recent numerical work by us and others, however, have determined that SC is absent within the ρ = 1 triangular lattice Hubbard model [25][26][27] and the earlier results are artifacts of mean-field approximations.…”
mentioning
confidence: 97%
“…17 Theoretically, the spin-liquid properties have been investigated on the basis of the anisotropic triangularlattice Hubbard Hamiltonian. 12,[18][19][20][21] The parameters t, t ′ and U of this Hamiltonian have been determined with semi-empirical 7 as well as first principles methods 22,23 based on the experimental structure at room temperature. Missing in such investigations is, however, the consideration of a possible temperature dependence of the model parameters.…”
Section: Introductionmentioning
confidence: 99%